CHARACTERIZATION OF SMALL-SCALE FISHERIES OF THE TAHUAYO RIVER: ECOLOGICAL BASES FOR FISHERIES MANAGEMENT WITH A BASIN APPROACH - MOYA-VÁSQUEZ, Luis (2020)
Small-scale fishing, such as that of the Tahuayo river basin (CRT) has been little studied despite its importance as a protein supply for the region. This article presents the fisheries' main ecological features in the CRT based on of an analysis of fish landings. Between August 2016 and July 2017, the richness and composition of species, biomass and catches per unit of effort (CPUE) were evaluated, by hydrological periods, aquatic environments and communities. The captures presented 62 species, grouped into 23 families and 7 orders, with the Pimelodidae family being the most diverse (12 species). Species richness was very similar between hydrological periods and between aquatic environments. The total landing amounted to 13,805.38 kg, where 17 species represented 80.5% of the biomass. More than 50% of the biomass was landed in periods oflow-water, mainly in the community of El Chino (71.5%). The average annual CPUE for the CRT was 0.51 kg / hp (DE=0.046), obtaining the lowest catches in the high-water season and in streams (KW, p-value <0.05). The most captured species were the carachamas, the large catfish, the acarahuazú and the paco, with the highest catches being in the low-water season. All these results show the importance of considering small-scale fishing dynamics, under a basin approach that considers a diverse group of fish, different aquatic environments and their dynamics throughout the hydrological cycle.